The Relationship Between Body Image Satisfaction and School Connectedness: The Moderating Role of Gender - Kharisa Hasna Utami (South Sulawesi Education Development (SSED), 2024)
Adolescence is a period of transition where individuals ages 11 – 19 face developmental changes in every aspect of their lives. As adolescents experience physical, cognitive, and psychosocial changes, they are prone to various societal problems, such as body image problems. Being dissatisfied with the way they look could lead adolescents to change their appearance, both in a healthy and unhealthy way. These feelings of dissatisfaction could also affect multiple aspects of their lives, including how they connect with their school. This study aims to explore the relationship between body image satisfaction and school connectedness using the translated and adapted version of the Body Image Satisfaction Scale (BISQ) and School Connectedness Questionnaire (SCQ). This quantitative study collected data from participants ages 16 – 19 across Indonesia (n=112). Align with what is previously hypothesized, this research concluded that body image satisfaction significantly predicts school connectedness (R2 = .09, F (1,110) =12.015, p <.001). An additional analysis on gender was conducted. However, this study failed to prove the role of gender in moderating the relationship between body image satisfaction and school connectedness (b=-.07, t(108)=-1.19, p>0.001). The result from this research also indicates that a large number of Indonesian adolescents are unhappy with their body appearance and body shape. As body image satisfaction significantly predicts school connectedness, this research recommends school-based interventions and in-school campaigns that could promote a healthier body image in adolescents and create a safe space for adolescents to address their concerns regarding the way they look and feel.